Membentuk Karakter dengan Mempengaruhi Psikologi pada Anak dari Dampak Perceraian Orang Tua - Ridho Mai Rizky; Vinny Meilinda; Tiara Yulanda (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
The family is the first and main environment for a child to receive education, guidance and instill different values ​​and norms and develop various behaviors that are important for personal life, family and the environment. Parental division will lead to arguments and anger so that these emotions will tend to dominate the child's emotions. Based on the explanation above, researchers are interested in studying the impact of parental divorce on children's character. This research seeks to reveal how character formation influences children's psychology from the impact of parental divorce. In this research, descriptive qualitative methods were used. because to explore a particular case by conducting data mining to understand the case in detail (Tobing, H. et al., 2016). Researchers try to understand events or phenomena regarding the impact of parental divorce on the formation of children's character. According to Moh. Nazir (1988).